Convenient route for Au@Ti-SiO2 nanocatalyst synthesis and its application for room temperature CO oxidation - Soni, Yogita; Kumar, Anumol Erumpukuthical Ashok; Nayak, Chandrani; Deepak, Francis Leonard; Vinod, C. P. (Journal of Physical Chemistry C, 2017)
Small gold nanoparticles.of size less than 5 nm encapsulated inside titanium modified silica shell have been reported. Here, a modified sol-gel method, which is a one-step process, produces Au@Ti-SiO2 nanocatalyst with a good control of titanium loading. With a titanium loading of 0.9 and 2.2 wt % in silica, unprecedented low temperature activity (full conversion) is observed for this catalyst for CO oxidation reaction compared to Au@SiO2 catalyst. A combination of optimum sized gold nanoparticles with a large amount of oxygen vacancies created due to Ti incorporation in silica matrix is considered to be the reason for this enhanced catalytic activity. The size of.gold nanoparticles is maintained even after high temperature pretreatments, which show the benefit of encapsulation. The effect of the various pretreatments on the catalytic activity has also been reported.

Understanding alloy structure and composition in sinter-resistant AgPd@SiO2 encapsulated catalysts and their effect on catalytic properties - Mondal, Sourik; Rajesh, Thattarathody; Dhar, Basab B.; Snellman, Markus; Li, Junjie; Deepak, Francis Leonard; Devi, R. Nandini (New Journal of Chemistry, 2017)
The extent of alloying and the alloy composition, which are crucial in determining the activity and selectivity of bimetallic catalysts, were studied in porous silica encapsulated AgPd catalysts using XRD, HRTEM and HAADF-STEM. Water-dispersible ligand protected Pd ultra-small clusters and Ag nanoparticles of three different sizes were used as the precursors. The high reactivity of Pd ultra-small clusters enhanced the alloying of larger Ag nanoparticles to some extent. Encapsulation appeared to have minimised the sintering of the resultant nanoparticles. The earlier suggestions of the role of d-band positions with respect to adsorption energies holds good for the AgPd system and alloying enhances the activity. Alloy with the composition of Ag50Pd50 was found to be the most active with the reaction rate enhanced two fold compared to that in other compositions. Other factors like particle size and sinter-resistance also played important roles in enhancing the activity of these catalysts.

Mesoporous shell@macroporous core aluminosilicates as sustainable nanocatalysts for direct N-alkylation of amines - Sekhar, Anandakumari C. Sunil; Ashokkumar, Anumol Erumpukuthickal; Cygnet, Choorapoikayil T.; Lakshmi, Saseendranpillai Vidhya; Deepak, Francis Leonard; Vinod, Chathakudath P. (Chemnanomat, 2018)
Aluminosilicate spheres with a macroporous core and mesoporous shell (Si/Al ratio of 11) is synthesised by a sol-gel method utilizing cetyltrimethyl ammonium bromide (CTAB) as a structure directing agent in basic medium. The selective incorporation of aluminium in the silica matrix results in the formation of aluminosilicates with an overall acidity of 0.32mmol/g with interconnected pores. Direct N-alkylation reaction is a prototype of C-N bond formation reaction and meso- macroporous aluminosilicate is shown to catalyze this reaction with excellent yield. The catalyst is tested and found sustainable for five catalytic cycles even without any high temperature regeneration step.
Keywords: Aluminosilicates; macroporous; Mesoporous; N-alkylation; nanocatalysis

Understanding alloy structure and composition in sinter-resistant AgPd@SiO2 encapsulated catalysts and their effect on catalytic properties (vol 41, pg 14652, 2017) - Mondal, Sourik; Rajesh, Thattarathody; Dhar, Basab B.; Snellman, Markus; Li, Junjie; Deepak, Francis Leonard; Devi, R. Nandini (New Journal of Chemistry, 2020)

Mechanistic insights into near ambient pressure activity of intermetallic NiZn/TiO2 catalyst for CO2 conversion to methanol - Dongapure, Pavan; Tekawadia, Jyoti; Thundiyil, Shibin; Caha, Ihsan; Deepak, Francis Leonard; Devi, R. Nandini (ChemCatChem, 2023)
Ni-Zn pair is predicted through descriptor-based studies to be conducive for CO2 hydrogenation. In this study, NiZn (1 : 1) intermetallics supported on TiO2 is identified as a potential candidate for near ambient pressure activity. The effect of reduction temperature on the catalyst textural properties as well as on CO2 to methanol reduction are explored. Structural and microscopic studies provide clear evidence of phase evolution of NiZn alloy with increasing reduction temperatures, along with phase variations of Zn based oxides. Interface between NiZn intermetallics and ZnO nanoparticles observed at reduction temperature of 550 degrees C, seems to play a crucial role in making this system most active and selective to methanol. In addition, in-situ IR studies provide mechanistic insights and indicates the formation of methanolic species even at ambient pressure.
Keywords: CCUS; CO2; In-situ IR; Methanol; near ambient pressure